2014
DOI: 10.1177/1545968314521006
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation Delivered During Motor Rehabilitation Improves Recovery in a Rat Model of Stroke

Abstract: Neural plasticity is widely believed to support functional recovery following brain damage. Vagus nerve stimulation paired with different forelimb movements causes long-lasting map plasticity in rat primary motor cortex that is specific to the paired movement. We tested the hypothesis that repeatedly pairing vagus nerve stimulation with upper forelimb movements would improve recovery of motor function in a rat model of stroke. Rats were separated into three groups: vagus nerve stimulation during rehab, vagus n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
136
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(161 citation statements)
references
References 32 publications
19
136
0
Order By: Relevance
“…VNS paired with rehabilitative training significantly improved recovery of volitional forelimb strength compared with rehabilitative training without VNS after TBI. Consistent with previous studies, VNS did not reduce lesion size, suggesting that VNS does not improve motor recovery through gross neuroprotection [59,60,75]. These findings extend the efficacy of VNS paired with rehabilitative training to a model of TBI.…”
Section: Preclinical Studies For Traumatic Brain Injurysupporting
confidence: 89%
See 3 more Smart Citations
“…VNS paired with rehabilitative training significantly improved recovery of volitional forelimb strength compared with rehabilitative training without VNS after TBI. Consistent with previous studies, VNS did not reduce lesion size, suggesting that VNS does not improve motor recovery through gross neuroprotection [59,60,75]. These findings extend the efficacy of VNS paired with rehabilitative training to a model of TBI.…”
Section: Preclinical Studies For Traumatic Brain Injurysupporting
confidence: 89%
“…Although chronic VNS is known to confer anxiolytic effects [99,100], this effect is not dependent on pairing with an extinction training regimen. Therefore, the absence of benefits of unpaired VNS is consistent with VNS therapies for sensory and motor dysfunction described above [32,59,61], and further supports enhancement of plasticity as a convergent mechanism that underlies the benefits of VNS therapy.…”
Section: Preclinical Studies For Post-traumatic Stress Disordersupporting
confidence: 74%
See 2 more Smart Citations
“…Vagus nerve stimulation (VNS) is a minimally invasive neuroprosthetic approach that might be used to provide tight temporal and circuit-specific modulation of brain areas and synapses engaged in an ongoing task. A series of recent studies from Michael Kilgard's group at The University of Texas at Dallas have shown that pairing VNS with discrete sensory or motor stimuli (e.g., a tone or a lever pull) is highly effective in promoting cortical plasticity to treat tinnitus 7 , or to overcome motor deficits following stroke [8][9][10] . In addition, non-contingent VNS that occurs within a short time-window after learning similarly promotes cortical plasticity and enhances memory consolidation in rats and in humans [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%